EUROPEAN COHESION POLICY IN LIGHT OF LEON PETRAZYCKI’S CONCEPT OF LEGAL POLICY - Jaśkiewicz, Jacek Tomasz (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
Abstract Leon Petrażycki’s concept of legal policy, based on author’s original assumptions, focuses on the social and economic legal actions aiming to the general social prosperity. Legal policy was strictly connected with the idea of the real acceptance of the law, understood by the author as a specific socio-psychic mental state, approved in an individual experience and confirmed in a social practice. Petrażycki as the first law theorist so clearly emphasised the meaning of multiplicity of legal sources and economical nature of law and the necessity to acknowledge various languages and local cultures in its contents. This concept, made far ahead of Petrażycki’s lifetime, contains a lot of solutions which are convergent with one of the most important European policies – EU cohesion policy. The objectives, assumptions and sources of cohesion policy, located at the junction of traditionally understood law-making, application of law and social and economic politics, are surprisingly similar to Petrażycki’s program. The author focuses on the subject of these relations.